A functional connection between translation elongation and protein folding at the ribosome exit tunnel in Saccharomyces cerevisiae. Issue 1 (16th December 2020) - Rodríguez-Galán, Olga; García-Gómez, Juan J; Rosado, Iván V; Wei, Wu; Méndez-Godoy, Alfonso; Pillet, Benjamin; Alekseenko, Alisa; Steinmetz, Lars M; Pelechano, Vicent; Kressler, Dieter; de la Cruz, Jesús
Abstract: Proteostasis needs to be tightly controlled to meet the cellular demand for correctly de novo folded proteins and to avoid protein aggregation. While a coupling between translation rate and co-translational folding, likely involving an interplay between the ribosome and its associated chaperones, clearly appears to exist, the underlying mechanisms and the contribution of ribosomal proteins remain to be explored. The ribosomal protein uL3 contains a long internal loop whose tip region is in close proximity to the ribosomal peptidyl transferase center. Intriguingly, the rpl3 [W255C] allele, in which the residue making the closest contact to this catalytic site is mutated, affects diverse aspects of ribosome biogenesis and function. Here, we have uncovered, by performing a synthetic lethal screen with this allele, an unexpected link between translation and the folding of nascent proteins by the ribosome-associated Ssb-RAC chaperone system. Our results reveal that uL3 and Ssb-RAC cooperate to prevent 80S ribosomes from piling up within the 5′ region of mRNAs early on during translation elongation. Together, our study provides compelling in vivo evidence for a functional connection between peptide bond formation at the peptidyl transferase center and chaperone-assisted de novo folding of nascent polypeptides at the solvent-side of the peptide exit tunnel.